IDEOLOGICAL TRAP IN EDUCATION: Rivalry Discourse on Islamic Literatures in NW and Salafi Schools in Lombok - Saparudin, Saparudin (TARBIYA: Journal of Education in Muslim Society, 2022)
AbstractThis study aimed to analyze the ideological contestation between the Nahdlatul Wathan (NW) as a local Islamic group and Salafis as a transnational Islamic group in the Islamic literature, which is utilized as teaching materials in NW and Salafi schools. The rivalry between these two religious groups become a novel phenomenon in Lombok together with the increasing influence of the Salafi group. The success of Salafis in promoting the manhaj salaf, which in many ways contradicts the Aswaja promoted by NW in Islamic practice, has implications for the strengthening of the ideological content in Islamic textbooks in their respective schools. Acoording to the data characteristic this study is library research sourced from several Islamic works of literature utilized as teaching materials in NW and Salafi schools. Based on the identification of literature books utilized as teaching materials, as analyzed based on the contestation theory by Antje Wiener and apparatuses of ideology theory by Louis Althusser, this study argues that religious literature used as teaching materials in Islamic schools is an instrument of ideological trapping of religious groups to generate apparatuses of ideology to win the contestation. The teaching materials contain negation of one another, mono-interpretation, and misleading one another. Finally, students only accept particular religious understandings indoctrination without being taught to think critically regarding different religious perspectives. In this context, a state polyce is needed to makesure that the higher order thinking skills of students have been developing, rather than ideological traping of certain Islamic group.AbstrakPenelitian ini bertujuan untuk menganalisis persaingan ideologis antara NW sebagai kelompok Islam Lokal, dan Salafi sebagai kelompok Islam transnasional dalam literatur keislaman yang dijadikan bahan ajar di sekolah NW dan Salafi. Persaingan kedua kelompok keagamaan ini menjadi fenomena baru di Lombok bersamaan dengan semakin berkembangnya pengaruh kelompok Salafi. Keberhasilan Salafi mempromosikan manhaj salaf yang dalam banyak hal bertentangan dengan Aswaja yang diusung NW dalam praktik keislaman, berimplikasi terhadap semakin menguatnya muatan ideologis dalam buku teks keislaman pada sekolah masing-masing. Sesuai karakteristik data, studi ini merupakan penelitian kepustakaan yang bersumber dari berbagai literature keislaman yang digunakan di sekolah NW dan Salafi. Berdasarkan identifikasi terhadap buku-buku literatur yang digunakan sebagai bahan ajar, yang dianalisis berdasarkan teori kontestasi oleh Antje Winner, dan teori apparatus ideology oleh Louis Althrusser, studi ini berargumen bahwa literatur keagamaan yang digunakan sebagai bahan ajar di sekolah Islam merupakan instrumen perangkap ideologis kelompok keagamaan untuk melahirkan apparatus ideologi demi memenangkan persaingan. Bahan ajar tersebut memuat penegasian satu dengan yang lain, mono-intrepretasi, dan saling menyesatkan satu dengan yang lain. Akhirnya, siswa hanya menerima indoktrinasi paham keagamaan tertentu, tanpa diajarkan berpikir kritis terhadap perbedaan pandangan keagamaan. Maka dibutuhkan intervensi Negara untuk memastikan berpikir kritis siswa harus tumbuh dalam dunia pendidikan Islam, tanpa dikukung oleh ideology kelompok tertentu.How to Cite: Saparudin. (2022). Ideological Trap in Education: Rivalry Discourse on Islamic Literatures in NW and Salafi Schools in Lombok. TARBIYA: Journal of Education in Muslim Society, 9(2), 20-35. doi:10.15408/tjems.v9i1. 24837.